Pius XII, the Holocaust, and the revisionists : essays - Gallo, Patrick J. (Jefferson, N.C. : McFarland & Co., Inc., Publishers, 2006)
"Through a series of articles and essays, the editor and eight contributors critique the works of revisionists who allege that Pius XII was sympathetic to the Nazis or unresistant to their atrocities. The essays discuss the roots of these views in the relentless Nazi and communist propaganda of the era"--Provided by publisher.
Includes bibliographical references (p. 187-211) and index.
Keywords: Pius -- XII, -- Pope, -- 1876-1958 -- Relations with Jews; Catholic Church -- Relations -- Judaism; Holocaust, Jewish (1939-1945); Judaism -- Relations -- Catholic Church; Christianity and antisemitism -- History -- 20th century; World War, 1939-1945 -- Religious aspects -- Catholic Church; National socialism and religion